2015
DOI: 10.3892/ijo.2015.3226
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 suppresses E-cadherin expression in nasopharyngeal carcinoma cells by enhancing E-cadherin promoter DNA methylation

Abstract: Nasopharyngeal carcinoma (NPC) has the highest metastasis potential among head and neck cancers. Distant metastasis is the major cause of treatment failure. Recent studies from our laboratory have revealed that IL-8 promotes NPC metastasis via activation of AKT signaling and induction of epithelial-mesenchymal transition (EMT) in the cells. In the present study, we found that IL-8 treatment for NPC cells resulted in an accumulation of DNMT1 protein through activating AKT1 pathway and consequent DNMT1 protein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…Next, we explored the concurrence of stem-like cell properties with the EMT process in the MDA-MB-231 cell line, as we have observed in cytokine-treated MCF-7, and as it has been reported in other cancer models [6772]. Unexpectedly, cytokine pre-treated MDA-MB-231 cells do not form mammospheres, but instead cell aggregates, that were very irregular, translucent and of different size (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Next, we explored the concurrence of stem-like cell properties with the EMT process in the MDA-MB-231 cell line, as we have observed in cytokine-treated MCF-7, and as it has been reported in other cancer models [6772]. Unexpectedly, cytokine pre-treated MDA-MB-231 cells do not form mammospheres, but instead cell aggregates, that were very irregular, translucent and of different size (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…81 In addition, one study showed that the IL-8/ AKT1 pathway regulated E-cadherin expression by stabilizing DNMT1 protein, thus enhancing hypermethylation of the Ecadherin promoter. 82 These data suggest that both hypomethylation and hypermethylation of related genes are critical for the modulation of the process of cancer metastasis.…”
Section: Dna Methylation Dysregulation In Cancer Metastasismentioning
confidence: 94%
“…Finally, Zhang et al . () have recently shown that, in nasopharyngeal carcinoma cells, IL‐8 stabilizes the DN methyl‐transferase DNMT1 via AKT, thereby inducing methylation of E‐cadherin promoter, leading to E‐cadherin repression and EMT program activation. Cooperative induction of EMT in colorectal cancer cells has been shown upon IL‐8 and CCL20 treatment, in conditions in which each individual treatment failed to induce EMT.…”
Section: Emt and Soluble Factors Of Inflammationmentioning
confidence: 99%